Kajian Ios Apps dalam Peningkatan Produktifitas Perancangan Arsitektur - Tomasowa, Riva (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The use of mobile device with sophisticated hardware and smart apps is a robust tool in terms of improving productivity nowadays, as well as to the dynamic architecture design process. The communication is not merely limited to formal audio and visual, but also bridges the data synchronisation, time and distance. However, this novel technology is not fully adopted to support the design process. This paper describes the built iOS apps which designed to aid the architects and then compares their potential on each design phases. Discussion of the analysis based on the design flow of the feasibility study (feasibility study) to facilitymanagement - FM, which discusses the ability of CAAD in the design stage. In brief, the research shows the absence of rigid framework for interoperability that could accommodate two ways information exchange between apps and desktop applications.